Applying the tilt‐depth and contact‐depth methods to the magnetic anomalies of thin dykes. (19th July 2016) - Cooper, G.R.J.
ABSTRACT: A new method for the calculation of the depth, location, and dip of thin dykes from pole‐reduced magnetic data is introduced. The depth can be obtained by measuring the distance between chosen values of a tilt angle that is based upon the ratio of the magnetic field and its Hilbert transform over the dyke. Alternatively, it can be obtained from the horizontal derivative of the ratio of the Hilbert transform of the field to the field itself, over the dyke. The latter method also allows the dip of the dyke to be estimated from the gradient of the depth estimates.